Strengthening Accounting Information Systems with Advanced Big Data Mining Algorithms: Innovative Exploration of Data Cleaning and Conversion Automation - Yang, Shu (Informatica, 2025)
With the rapid development of big data technology, accounting information systems are facing unprecedented challenges in processing and analyzing massive financial data. In order to improve the efficiency and accuracy of data processing, this article deeply explores the application of big data mining algorithms in optimizing accounting information systems. By introducing advanced big data mining algorithms, accounting information systems have achieved automation in data cleaning, transformation, and analysis, significantly reducing manual intervention and improving data processing efficiency. This article compares the performance of different big data mining algorithms in the analysis of accounting informationization risk transactions. Through practical verification, we found that the selected algorithm performs well in terms of accuracy, reaching over 95%, which is a significant improvement compared to traditional methods. Meanwhile, in terms of computation time, the algorithm has also demonstrated significant advantages, reducing computation time by over 30% when processing datasets of the same size. These performance improvements not only improve the operational efficiency of accounting information systems, but also provide enterprises with more accurate and timely financial information. In addition, this article also conducted a survey on the intelligent management of accounting information systems. We collected valuable opinions on the current status of accounting information intelligent system management by distributing survey questionnaires to in-service MBA and MPAcc students. The survey results show that over 76% of accounting personnel and almost all management personnel (91.18%) agree with the intelligent features of accounting information systems and believe that establishing a separate accounting knowledge base or knowledge management system is necessary. This discovery further emphasizes the importance of optimizing accounting information systems and provides direction for future research.